The Role Of Small Micro Enterprises In Production Snack And Product Innovation Towards Additional Community Economic Income In Tangerang City - Heri Satrianto; Berlin Silaban; Rinintha Parameswari (Primanomics : Jurnal Ekonomi & Bisnis, 2021)
The study is intended to determine The Role of Small Micro Enterprises in Production Snack and Product Innovation towards an Additional Community Economic in Tangerang City. Micro small and medium enterprises (MSMEs) have an important role in the economy of Indonesian society. Indonesia government also views the existence of MSME businessman as important. The existence of MSMEs can have an effect on increasing people's income and also with the innovation of snacks that can attract consumers. The method used quantitative which was taken, it can be conclude that Whereas t count is 6,453> t table is 1,985 and the sig o.oo value <0.05, this shows that the role of Micro and Small Enterprises in production snacks has a significant and positive effect on the addition of community economic income in Tangerang City. That t count is 5,568> t table is 1,985 and the sig o.oo value <0.05, this shows that product innovation has a significant and positive effect on the addition of community economic income in Tangerang City. Whereas F count is 161,927> from F table of 3.09 and sig value of 0,000 <0.05, this shows that the Micro and Small Entrepreneurs Production snacks together with product innovation have a significant and positive effect on the addition of community economic income in Tangerang City.